2021
DOI: 10.1021/acs.jpca.1c06815
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Study of Triflic Acid Hydrates: Evidence for the Transition from Hydrogen-Bonded Clusters to a Microsolvated Ion Pair

Abstract: Rotational spectra of the mono-, di-, and trihydrates of triflic acid, CF 3 SO 3 H•••(H 2 O) n=1−3 , have been recorded by pulsed nozzle Fourier transform microwave spectroscopy and spectroscopic constants obtained have been compared with values calculated at several levels of theory. The experimental results are consistent with the theoretical predictions presented here and elsewhere, indicating that with only one or two water molecules, triflic acid remains un-ionized in a cold molecular complex. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…14 Besides, charge distributions and structural changes can be observed to be prominent dependent on stepwise complexation with H 2 O. 15,16 Indeed, it has been shown that the bond lengths r(Na-Cl) increase with the growth of the number of water molecules. The structure of NaCl-(H 2 O) 3 is approaching that of the contact ion-pair, which is considered to be an intermediate species in the incipient solvation process.…”
Section: Introductionmentioning
confidence: 99%
“…14 Besides, charge distributions and structural changes can be observed to be prominent dependent on stepwise complexation with H 2 O. 15,16 Indeed, it has been shown that the bond lengths r(Na-Cl) increase with the growth of the number of water molecules. The structure of NaCl-(H 2 O) 3 is approaching that of the contact ion-pair, which is considered to be an intermediate species in the incipient solvation process.…”
Section: Introductionmentioning
confidence: 99%
“…These differences likely reflect the relative acidities of triflic acid and MSA. In this regard, it is satisfying to note that, at the M06-2X/6-311++G(3df,3pd) level of theory, the primary hydrogen bond (O9···H10) in the triflic acid monohydrate is 1.58 Å, which is somewhat shorter than the 1.66 Å distance in MSA–water obtained from the calculations reported here. The two lowest-energy conformers for MSA–water and triflic acid–water are very similar, structurally.…”
Section: Discussionmentioning
confidence: 99%
“…Microwave spectra of triflic acid and its −OD isotopologue have been reported and reveal a tunneling motion arising from the wagging of the −OH­(D) moiety between two equivalent minima on either side of a C s symmetric transition state. The hydrates of triflic acid, CF 3 SO 3 H···(H 2 O) n =1–3 , as well as its complex with trimethylamine, have also been investigated by microwave techniques. These studies have shown that triflic acid undergoes proton transfer when complexed with only one trimethylamine molecule but requires three water molecules to realize proton transfer in a cold molecular complex.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, increasing the strength of the acid should further increase the degree of proton transfer to any given base. Indeed, with the superacid triflic acid (CF 3 SO 3 H), complete or near-complete proton transfer been demonstrated in a 1:1 complex with N­(CH 3 ) 3 9 and in its complex with three water molecules …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with the superacid triflic acid (CF 3 SO 3 H), complete or near-complete proton transfer been demonstrated in a 1:1 complex with N(CH 3 ) 3 and in its complex with three water molecules. 10 In this paper, we report a microwave and computational study of the complex formed from trifluoroacetic acid (F 3 CCOOH, TFA) and trimethylamine (N(CH 3 ) 3 , TMA). Trimethylamine is a strong amine base and TFA is a stronger acid than most carboxylic acids (pK a = 0.47 at 298 K from an average of several literature values).…”
Section: ■ Introductionmentioning
confidence: 99%